1987
DOI: 10.1111/j.1439-0450.1987.tb00425.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Levels in Milk of Vaccinated and Unvaccinated Cows against Organisms of Neonatal Diarrhoea

Abstract: Summary The development of antibody levels in colostrum and milk in 10 cows vaccinated twice subcutaneously in the dry period at an interval of 4 weeks with Lactovac® was investigated in a controlled study. Antibody levels to all five antigens involved were higher than those in 10 unvaccinated controls on days 1, 4, 7, 10 and 14 after calving. The degree of the increase differed from quota to quota and became smaller overall up to day 14. The greatest average increases were observed for the E. coli K 99 at 26.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
1
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
0
3
1
1
Order By: Relevance
“…These results agree with those of Acres and others (1979), Nagy (1980), Snodgrass and others (1980, 1982), Hess and others (1982), Castrucci and others (1984), Saif and others (1984) and Snodgrass (1986) who showed that the vaccination of cows with either E coli F5 (K99) antigen or rotavirus antigen alone or in combination induced levels of antibody in the milk which could provide significant protection against challenge. However, previous studies (Dauvergne and others 1983, Stepanek and others 1987, Wieda and others 1987, Mostl and Burkl 1988, Kohara and others 1997) have described only minimal increases or no increases in the levels of coronavirus antibody in either serum or milk after the vaccination of cows with preparations containing inactivated bovine coronavirus antigen, whereas the vaccine used in this study produced a significantly enhanced antibody response in the milk. The reasons for this difference are unclear but are most likely to be associated with the levels of coronavirus antigen incorporated into this new vaccine and the use of a highly effective adjuvant (Crouch 1985).…”
Section: Methodscontrasting
confidence: 52%
“…These results agree with those of Acres and others (1979), Nagy (1980), Snodgrass and others (1980, 1982), Hess and others (1982), Castrucci and others (1984), Saif and others (1984) and Snodgrass (1986) who showed that the vaccination of cows with either E coli F5 (K99) antigen or rotavirus antigen alone or in combination induced levels of antibody in the milk which could provide significant protection against challenge. However, previous studies (Dauvergne and others 1983, Stepanek and others 1987, Wieda and others 1987, Mostl and Burkl 1988, Kohara and others 1997) have described only minimal increases or no increases in the levels of coronavirus antibody in either serum or milk after the vaccination of cows with preparations containing inactivated bovine coronavirus antigen, whereas the vaccine used in this study produced a significantly enhanced antibody response in the milk. The reasons for this difference are unclear but are most likely to be associated with the levels of coronavirus antigen incorporated into this new vaccine and the use of a highly effective adjuvant (Crouch 1985).…”
Section: Methodscontrasting
confidence: 52%
“…This Ig transfer capacity limit and the necessity t o protect the immuno-incompetent newborn (BANKS, 1982) are the reasons for passive immunization of calves by vaccination of pregnant cows, whereby the absorption capacity of the calf is optimally used for specific antibodies. Research work in this field has been re-commenced recently, and the pathogens studied include rotaand corona-parvovirus, and E. coli K 99 (EICHHORN et al, 1982;BACHMANN et al, 1985;WIEDA et al, 1987;BENGELSDORF et al, 1987). Vaccination against S. dublin and S. typhimurium has been investigated by MEYER et al (1993) and by STAAK et al (1989STAAK et al ( , 1990.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies demonstrated that continuous feeding of colostrum from immunized cows prevented severe diarrhea and death in calves [1,10,12,14,18]. In North America and Europe, various maternal vaccines against calf diarrhea to enhance antibody titers in the colostrum and milk of cows have been developed [7,11,14,17,20]. By contrast, there are few reports on maternal vaccination to protect against calf diarrhea in Japan.…”
mentioning
confidence: 99%
“…The calves were reared on their mothers. A commercial combination vaccine (Lactovac; Hoechst, Germany) was used [20], which contained inactivated group A BRV V1005/78 [G serotype 10 (G10), P genotype 5 (P5)] and Holland [G serotype 6 (G6), P genotype 1 (P1)] strains at both titers 10 7.5 TCID 50 /5 ml, BCV 800 strain at titer 10 7.5 TCID 50 /5 ml, bovine parvovirus (BPV) Haden strain at titer 10 7.7 TCID 50 /5 ml and E. coli-K99 pilus antigen at titer 512 HU/5 ml. The 48 pregnant cows were inoculated subcutaneously in the side of the neck with 5 ml of the vaccine at 6 to 11 weeks before calving.…”
mentioning
confidence: 99%